CGIAR Climate Impact Platform influences the climate agenda through participation in high profile global discourses on climate change and agri-food systems all throughout 2024 - Edward-Uwadiale, Regina; Smith, Georgina (CGIAR System Organization, 2024)
CGIAR scientists amplify global food system transformation insights through 18 speaking engagements outside COP29 and 25 within COP29 to influence the global agenda.